Wide Voltage Gain Range Enhanced Cubic Boost Converter With Reduced Components Voltage Stress - Vemparala Seshagiri Rao; M. S. Bhaskar; Mahmoud F. Elmorshedy; Dhafer Almakhles (IEEE Access)
In conventional boost and quadratic boost converters, achieving the required output voltage necessitates a higher duty ratio. Additionally, these converters require switch and load diode ratings equal to the output voltage, which increases switching losses and reduces converter efficiency. This paper introduces an enhanced cubic boost converter (ECBC) to address these drawbacks. The ECBC can achieve a wide voltage gain range, allowing the converter to operate at a lower duty ratio and reducing voltage stress across the components. Consequently, it is possible to select components with lower ratings, thus improving the performance of the ECBC. This paper details the steady-state operation of both continuous and discontinuous conduction modes (CCM and DCM) and examines the effects of parasitic elements on voltage gain and efficiency. The performance of the ECBC is compared with the characteristics of conventional converters. Using the state space averaging technique, the small signal model of ECBC is developed, and the PI controller is designed to improve the dynamic response. An experimental model with an output voltage of 400 V was built to validate the operation and confirm the theoretical analysis with experimental results.